Cotidianies in Latin America: Concepts, Genres, Contrasts - Deves-Valdes, E (UNIV SANTIAGO CHILE, INST ESTUDIOS AVANZADOS, 2021)
This work deals with the emergence and consolidation of new eidetic expressions in contemporary reality. Thus, a set of " isms" that can be grouped into the "cotidiany" notion are studied. Cotidiany is an eidetic genre (or species) that distinguishes itself from ideologies, philosophical systems, scientific paradigms, and "ideoglobies", among many others. To account for "cotidianies", three cases of "purification of personal-daily life" present at the beginning of the 21st century are shown, describing their fundamental notions, and looking for similarities and differences. The hypothesis developed is that cotidianies are eidetic expressions whose meaning is achieved in the possibility of improving existence in its daily dimension, assuming that this is possible in the context of the individual, making few or no references to the socio-economic-political reality, but without ruling out collective or community dimensions. It should be added that the notion "improving existence" has in cotidianies an eminently psychic-bodily sense, non-economic, non- social rise, nor of hegemony-although all those matters are not excluded in principle-. It also argues about the need to open up studies of ideas into expressions of the eidetic, since these expressions are very little considered by the community of those who study these topics.